Radio communautaire et espace dans le Mexique néolibéral - Eduardo González Castillo (Communication)
This paper focuses on community radio in contemporary Mexico. Written from the perspective of political economy, the article focuses on the neoliberal context that conditions the existence of community radios in that country. Special attention is given, in the analysis, to the spatial dimension of broadcasting. The analysis is structured around the concepts of absolute, relative and relational space, proposed by David Harvey, geographer.